2015
DOI: 10.1042/cs20150073
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of adipocyte fatty-acid-binding protein alleviates myocardial ischaemia/reperfusion injury and diabetes-induced cardiac dysfunction

Abstract: Clinical evidence shows that circulating levels of adipocyte fatty-acid-binding protein (A-FABP) are elevated in patients with diabetes and closely associated with ischaemic heart disease. Patients with diabetes are more susceptible to myocardial ischaemia/reperfusion (MI/R) injury. The experiments in the present study investigated the role of A-FABP in MI/R injury with or without diabetes. Non-diabetic and diabetic (streptozotocin-induced) A-FABP knockout and wild-type mice were subjected to MI/R or sham inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…The reperfusion therapy with blood flow restoration is the recommended treatment for infarct recovery, yet is more curative for ischaemia of short duration 1, 2. Moreover, reperfusion paradoxically leads to additional damage to ischaemic myocardium 2, 3.…”
Section: Introductionmentioning
confidence: 99%
“…The reperfusion therapy with blood flow restoration is the recommended treatment for infarct recovery, yet is more curative for ischaemia of short duration 1, 2. Moreover, reperfusion paradoxically leads to additional damage to ischaemic myocardium 2, 3.…”
Section: Introductionmentioning
confidence: 99%
“…FABP4 has a well-established role in the development and progression of diabetes and atherosclerosis, [15][16][17]19,20 but the effect of FABP4 in AKI has not been determined. Our study reported for the rst time that overexpression of FABP4 in kidneys, mainly expressed in tubular cells was induced by AKI aer I/R surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that FABP4 is also expressed in cardiomyocytes, and the overexpression of cardiac FABP4 exacerbates the cardiac hypertrophic response induced by pressure overload (Zhang et al 2016). Conversely, FABP4 deficiency attenuates ischaemia-/reperfusioninduced myocardial injury and improves LV function in both non-diabetic and streptozotocin-induced diabetic mice (Zhou et al 2015). Therefore, FABP4 secreted from epicardial fat tissue, subcutaneous and/or visceral adipose tissue or macrophages may influence heart dysfunction in a paracrine or endocrine manner.…”
Section: Fabp4 Cardiac Dysfunction and Hfmentioning
confidence: 99%